Different ways of problematising biotechnology – and what it means for technology governance. (July 2015) - Bogner, Alexander; Torgersen, Helge
To understand controversies over technologies better, we propose the concept of 'problematisation'. Drawing on Foucault's idea of problematisation and on the concept of frames in media research, we identify characteristic forms of problematising biotechnology in pertaining controversies, typically emphasising ethical, risk or economic aspects. They provide a common basis for disputes and allow participants to argue effectively. The different forms are important for how controversies are negotiated, which experts get involved, what role public engagement plays and how political decisions are legitimised – in short, for technology governance. We develop a heuristic for analysing the link between forms of problematisation and different options for technology governance. Applied to synthetic biology, we discuss different problematisations of this technology and the implications for governance.